2013
DOI: 10.1080/15504263.2012.750147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dual Disorders, Trauma, and Social Support on Quality of Life Among Women in Treatment for Substance Dependence

Abstract: Objective Women with dual disorders report lower levels of social support than women with substance dependence alone, and lower levels of social support have been associated with lower quality of life among individuals with substance use disorders. However, little is known about the impact of trauma symptoms and violence exposure on quality of life for women with dual disorders. The purpose of this study was to examine the impact of dual disorders, trauma, and social support related to recovery on various doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 46 publications
1
33
0
4
Order By: Relevance
“…In addition, women with dual disorders have more difficulty accessing and using social support (Tracy & Biegel, 2006), and experience less reciprocity within their network relationships (Tracy & Johnson, 2007) than women with a substance use disorder alone, making it difficult for them to realize the benefits that may derive from a supportive network. The high number of trauma symptoms among women with dual disorders (Najavits, Weiss, & Shaw, 1997) both impacts their ability to form positive close social attachments (Bollerud, 1990; Min, Tracy & Park, 2014) and their quality of life post treatment (Brown, Jun, Min & Tracy, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, women with dual disorders have more difficulty accessing and using social support (Tracy & Biegel, 2006), and experience less reciprocity within their network relationships (Tracy & Johnson, 2007) than women with a substance use disorder alone, making it difficult for them to realize the benefits that may derive from a supportive network. The high number of trauma symptoms among women with dual disorders (Najavits, Weiss, & Shaw, 1997) both impacts their ability to form positive close social attachments (Bollerud, 1990; Min, Tracy & Park, 2014) and their quality of life post treatment (Brown, Jun, Min & Tracy, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the USA revealed that women with mental illness and substance use perceived a worse quality of life specifically caused by symptoms associated with traumatic events, more than by the mental disorder itself …”
Section: Discussionmentioning
confidence: 99%
“…For example, promoting changes in personal network size and/or composition and developing more self-help groups are network interventions at the individual and family levels (Hogan, Linden, and Najarian, 2002; Richey, Lovell, and Reid, 1991). Interventions could also include helping women in distancing substance using family members from their non-using network members (Brown, Jun, Min, and Tracy, 2013; Brown, Tracy, Jun, Park, and Min, 2015). …”
Section: Discussionmentioning
confidence: 99%